The Medicine Wheel as a public health approach to lifestyle management interventions for indigenous populations in North America - Greer, Tammy; Lemacks, Jennifer L. (Frontiers in Public Health, 2024)
This analytic essay intends to elevate Medicine Wheel, or generally "four directions" teachings, to encourage a more comprehensive alignment of lifestyle intervention components with traditional ecological knowledge systems of Indigenous cultures in North America. North American Medicine Wheels provided people with a way to orient themselves both within their traditional belief systems and to the seasonal changes in their areas, improving survivability. The wheel or circle is a sacred symbol, indicating the continuity and perpetuity of all of life. The four directions are iconized in many Indigenous cultures across North America with different directions representing different aspects of our world and of ourselves, different seasons of the year and of our lives, different beings of the earth and tribes of humans with a balance among those necessary for health and wellbeing. In the context of public health, teachings of the four directions warn that a lack of balance limits our ability to achieve optimal health. While there is much public health success in lifestyle interventions, existing practice is limited by a siloed and one size fits all approach. Medicine Wheel teachings lay out a path toward more holistic and Indigenous-based lifestyle intervention that is modifiable depending on tribal teachings and needs, may appeal to a variety of Indigenous communities and is in alignment with health behavior change theory. It is a public health imperative that lifestyle management interventions are fully optimized to rigorously determine what can be achieved when interventions are implemented in a holistic and Indigenous-based manner, and in alignment with an Indigenous model of health. This more complete alignment would allow for a stronger foundation to further explore and develop social determinants (i.e., housing, employment, etc.) and structural intervention enhancements to inform public health practice and promote health equity.